Differences in clinical presentation and incidence of cardiopulmonary involvement in late-onset versus early-onset systemic sclerosis: inception cohort study - Suparaporn Wangkaew (2018)
© 2018 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Introduction: Data regarding the incidence rate (IR) of cardiopulmonary involvement in comparison between late-onset SSc and early-onset SSc are limited. Objective: To compare the prevalence of clinical manifestations and the IR of cardiopulmonary involvement compared between the two subgroups. Methods: An inception cohort of SSc patients seen at the Rheumatology Clinic, Maharaj Nakorn Chiang Mai Hospital, between January 2010 and June 2016, was used. All patients were assessed for clinical manifestations and underwent electrocardiograph, echocardiography and high-resolution computed tomography at the study entry and every 12 months thereafter. Result: One hundred and fifteen patients (69 female and 90 diffuse cutaneous SSc [dcSSc]) with a mean (SD) disease duration of 11.6 months (8.8) at cohort entry were enrolled during a mean (SD) observation period of 3.8 years (1.6). Patients were classified into two groups: age ≥ 50 years (late onset) and age < 50 years (early onset). The late-onset group included 78 patients (67.8%). At enrollment, the late-onset group had higher prevalence of digital pitting scars (60.3% vs. 35.1%, P = 0.012), dry eye symptoms (17.9% vs. 2.7%, P = 0.035), and hypertension (20.5% vs. 5.4%, P = 0.037) compared to the early-onset group. In the last visit, it was found that the late-onset group had higher cumulative prevalence of joint contracture (61.5% vs. 37.8%, P = 0.017) compared to the early-onset group. The late-onset group had no significant IR of left ventricular ejection fraction < 50% (3.04 vs. 4.45 per 100 person-years, P = 0.486), right ventricular dysfunction (5.17 vs. 2.73 per 100 person-years, P = 0.269), interstitial lung disease (49.45 vs. 42.03 per 100 person-years, P = 0.462), and systolic pulmonary arterial pressure ≥ 50 mmHg (2.57 vs. 1.07 per 100 person-years, P = 0.267) compared to the early-onset group. Conclusion: Our study cohort found that digital pitting scar, xerophthalmia, hypo–hyperpigmentation, joint contracture, and hypertension are more prevalent in late-onset SSc than early-onset SSc. However, no significant differences regarding the IR of cardiopulmonary involvement between the two subgroups, the majority of which were dcSSc, in the early phase of the disease.